Habit vs. intention in the prediction of future behaviour: the role of frequency, context stability and mental accessibility of past behaviour. - Danner UN; Aarts H; de Vries NK (British Journal of Social Psychology, 2008)
This research examined the role of habit and intention in the prediction of future behaviour by analysing that past behaviour frequency moderates the intention-behaviour relationship to the extent that the context in which the behaviour was performed is stable. In two correlational studies, it was found that habit interacted with intention when context stability was taken into account and not when merely past behaviour frequency was considered: intentions guided future behaviour when habits were weak (low frequency or unstable context), while this was not the case when habits were strong (high frequency and stable context). A third exploratory study investigated and confirmed the idea that, if habitual goal-directed behaviour is directly activated by the context, mental accessibility of the behaviour (i.e. the ease of accessing the goal-directed behaviour in memory) moderates the intention-behaviour relation in a similar way. These findings are discussed against the background of current research on goal-directed habits and the cognitive processes underlying them.